Return to COV&R 2021 - Gans, Eric Lawrence (2021)
It had been seventeen years since my last talk at COV&R, and given the Zoom connection, the physical distance was ironically maintained, although my location in Sugar Creek, MO was only about 480 miles from the Purdue conference center in West Lafayette, IN. After a scheduling mixup, I was able to give my talk on...